About the Book “History of the Tatars of the Western Cisuralic Region” - E.G. Sayfetdinova (Золотоордынское обозрение, 2016)
A collective monograph “History of the Tatars of the Western Cisuralic Region. Vol. I. The Nomads of the Great Steppe in the Cisuralic Region. Medieval Tatar States” [1] has been published by Sh.Marjani Institute of History (Kazan, 2016). The volume is dedicated to the medieval period and ends with the fall of the Kazan Khanate. The monograph has been prepared under the supervision of Doctor of Historical Studies, R.S. Khakimov. Editorial board of the monograph consists of leading scholars from academic centers in Russia and abroad. The book is divided into 4 chapters. The first chapter talks about the history of ancient nomads in the Cisuralic region. The second chapter examines the Volga-Kama Bulgaria and political unification of the Turkic nomads. The third chapter is dedicated to the formation of the Golden Horde state and the history of the formation of the Tatar people. The final fourth chapter discusses the Tatar khanates (Kazan and Siberian yurts, the Nogai Horde). An appendix including 55 narrative source is an important part of the collective monograph “History of the Tatars of the Cisuralic Region”. The authors of the first volume have not only succeeded to considerably fill the lacuna of historical knowledge about the Cisuralic Tatars, but also largely revise existing ideas about ethnogenesis of other Turko-Tatar and Finno-Ugric peoples in the region. This work does not provide all the answers. However, the important thing is that the authors of the monograph have succeeded to present new problems and outline prospects for further research. In the future, it is necessary to continue to study the process of ethnic migrations, which began in the Cisuralic region in the middle of the 16th century as well as the problems linked to the inclusion of these communities into the Russian state and other issues related to the history of the Cisuralic Tatars.